Adaptive Leadership Dinas Kesehatan Kota Surakarta Dalam Quality Service Akselerasi Vaksinasi Covid-19 - Rofi Aulia Azahra Putri; Gita Cinta Ramadhani; Noor Rizky Tiara Putri (Jurnal Kapita Sosial Politik, 2024)
Adaptive leadership is an important element for leaders in dealing with the Covid-19 pandemic in VUCA 5.0. One form of adaptive leadership carried out by the Surakarta City Health Office is implementing the Covid-19 vaccination acceleration program. This study was conducted to determine the adaptive leadership of the Surakarta City Health Office in the quality service acceleration of Covid-19 vaccination. This study uses a qualitative descriptive method with a case study in Surakarta City. The data collection technique uses the documentation study method and interview method with sources, the Head of the P2P Sub-Division of the Surakarta City Health Office, the Head of General Affairs and the Head of Administration of the Ngoresan Health Center. This study uses interactive data analysis techniques and shows that the adaptive leadership of the Surakarta City Health Office in the quality service acceleration of Covid-19 vaccination has been carried out in accordance with the aspects of anticipation, articulation, adaptation, and accountability. This can be seen from the achievement of the Covid-19 vaccination target by using various innovations in VUCA 5.0. The author provides recommendations to relevant stakeholders to continue the program and improve service innovation according to community conditions